2022
DOI: 10.5852/naturae2022a8
|View full text |Cite
|
Sign up to set email alerts
|

Crustacés (Decapoda, Stomatopoda) dans la zone mésophotique corallienne de Mayotte (Sud-Ouest Océan Indien)

Abstract: Des plongées techniques (TEK) en recycleur et mélanges gazeux spéciaux ont été réalisées autour de l’île de Mayotte sur les pentes externes récifales à des profondeurs comprises entre 50 et 120 m, et plus particulièrement aux alentours de 70-80 m, de 2017 à 2020. L’objectif de ces plongées était de réaliser un premier inventaire faunistique de la zone mésophotique, difficile d’accès et encore mal connue. Ce travail présente les résultats obtenus pour le groupe des Crustacés Décapodes et Stomatopodes avec au to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…CRUMMA is actively supported by the French Museum national d'Histoire naturelle, Paris (INPN, Inventaire National du Patrimoine Naturel), with a research grant obtained in 2021. Previous results include the discovery of a rare cavernicolous crab, Atoportunus dolichopus Takeda, 2003 (Barathieu et al, 2019) and a photograph inventory of 44 species observed in the mesophotic zone (Poupin et al, 2022). The description of the diving techniques and methodology used can be consulted in these previous contributions.…”
Section: Introductionmentioning
confidence: 99%
“…CRUMMA is actively supported by the French Museum national d'Histoire naturelle, Paris (INPN, Inventaire National du Patrimoine Naturel), with a research grant obtained in 2021. Previous results include the discovery of a rare cavernicolous crab, Atoportunus dolichopus Takeda, 2003 (Barathieu et al, 2019) and a photograph inventory of 44 species observed in the mesophotic zone (Poupin et al, 2022). The description of the diving techniques and methodology used can be consulted in these previous contributions.…”
Section: Introductionmentioning
confidence: 99%